Comparative evaluation of the effect of various endodontic irrigants on the push-out bond strength of endosequence, Biodentine™, and MTA Plus™ root repair materials: An in vitro study - Nitika Tiwari; Anamika C Borkar; Anita Tandale; Nikhil Nighot; Sailee Ghare; Sayali Maral (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aimed to evaluate and compare the effects of 2% chlorhexidine and 3% sodium hypochlorite (NaOCl) irrigating solutions on the push-out bond strength of EndoSequence, Biodentine™, and MTA Plus™ root repair materials. Materials and Methods: Teeth were decoronated, and the midroot was sectioned horizontally into slices with the thickness of 2.0 mm with the help of diamond discs. The canal space was enlarged to diameter of 1.4 mm with the help of Gates-Glidden Drill. The samples were divided into three groups (n = 12). EndoSequence, Biodentine™, and MTA Plus™ root repair materials were condensed in the canal space and allowed to set for 10 min. The three groups were further subdivided into two subgroups each. Each material was immersed in NaOCl and chlorhexidine gluconate (CHX), respectively, for 30 min, rinsed with distilled water, and allowed to set for 48 h at 37°C with 100% humidity in an incubator. The push-out bond strength value was then measured using a universal testing machine. Data obtained were statistically analyzed. Results: EndoSequence root repair material (ERRM) proved to have the highest push-out bond strength followed by Biodentine™ and MTA Plus™ root repair materials. In subgroups, CHX in contact with ERRM showed the highest push-out bond strength followed by NaOCl, whereas Biodentine™ when in contact with NaOCl showed more push-out bond strength than when in contact with CHX. MTA Plus™ in contact with CHX showed the least push-out bond strength. Conclusion: The push-out bond strength of ERRM significantly increased after exposure to NaOCl and has the highest push-out bond strength followed by Biodentine™, and MTA Plus™ has the least push-out bond strength.